PFAS concentrations and deposition in precipitation: An intensive 5-month study at National Atmospheric Deposition Program – National trends sites (NADP-NTN) across Wisconsin, USA. (15th December 2022) - Pfotenhauer, David; Sellers, Emily; Olson, Mark; Praedel, Katie; Shafer, Martin
Abstract: Atmospheric transport and processing of per- and polyfluoroalkyl substances (PFAS) leads to deposition and accumulation of these compounds in terrestrial and aquatic ecosystems, however, measurements of PFAS flux and deposition rates remain sparse and underdeveloped. In 2020, ninety-one precipitation samples, along with an array of QA/QC samples were collected from eight National Trends Network (NTN) sites across Wisconsin through the National Atmospheric Deposition Program (NADP). Weekly precipitation samples were analyzed for a suite of 34 PFAS compounds to provide measurements of speciated PFAS concentrations and deposition fluxes to in the Upper Great Lakes Region. Perfluoro carboxylates (PFCAs) were detected most frequently and constituted an average of 83% of the total mass quantified across the samples. Summed PFAS mass concentrations in the rainwater ranged from 0.7 to 6.1 ng/L with a median of 1.5 ng/L. Daily flux values ranged from 1.3 to 47.4 ng/m 2 /day with a median of 5.7 ng/m 2 /day. From an analysis of variance (ANOVA), significant differences in the average chemical profiles (PFAS fingerprints) were observed among the 8 sampling sites, indicating that nearby sources of PFAS can potentially influence wet-deposition composition of certain species on observed spatial scales. Strict quality control measures were developed and implemented for this study to confirm that the field and laboratory methods met the necessary high data quality standards. These methods and QA/QC protocols are detailed here to provide guidance for future wet deposition sampling of PFAS. This campaign confirms the efficacy of NADP-NTN samplers and protocols for the collection and study of PFAS atmospheric transport, deposition rates, and spatial trends in concentrations and flux. Highlights: 89 precipitation samples were collected across Wisconsin and analyzed for 34 PFAS compounds. The sums of quantified PFAS concentrations were typical of background levels. Differences among regional PFAS compound profiles indicate possible source influences. Yearly flux calculations provide first estimates of PFAS wet-deposition rates for Upper Midwest.